Description of a new genus of North and Central American planthoppers (Hemiptera: Fulgoridae) with fourteen new species - Yanega, Douglas; Goemans, Geert; Dam, Matthew Van; Gómez-Marco, Francesc; Hoddle, Mark (Zootaxa, 2024)
The fulgorid name Alphina glauca (Metcalf) has been used erroneously since its inception to refer to a primarily southeastern U.S. species described originally as Calyptoproctus marmoratus Spinola. Additionally, at least three undescribed species from the Southwest have been incorrectly identified as A. glauca. The holotype of A. glauca has not been located. Since A. glauca is presently used to refer to multiple species, a neotype is designated which places A. glauca into synonymy with Calyptoproctus marmoratus. We establish a new genus, Scaralina, into which it is placed, giving the new combination Scaralina marmorata (Spinola), along with three southwestern, one Texan, and ten Mesoamerican taxa, named here as new species: S. aethrinsula, S. chapina, S. cristata, S. durango, S. gigantea, S. hawksi, S. metcalfi, S. monzoni, S. obfusca, S. obrienae, S. orientalis, S. rileyi, S. sullivani, and S. veracruzensis. Additionally, one new species of Scaralis in a new subgenus, Scaralis (Alphinoides) inbio, is described from Costa Rica and Guatemala. The limited information available suggests these insects feed on oaks (Quercus). The single defining putative synapomorphy for the subtribe Calyptoproctina is the enlarged apical plate on the female abdomen, which is absent in at least two members of Scaralina, and is also present in some genera that belong outside of Poiocerinae, so we reject the recognition of this subtribe. We consider that Scaralina is probably more closely related to the genus Scaralis Stål than to Alphina Stål. Based on morphology, some species originally described in Scaralis appear to be more closely related to one another than to the type species of the genus, and are here placed in a new subgenus, Alphinoides; Scaralis fluvialis Lallemand and Scaralis nigronotata Stål, plus three species originally described in Poiocera; Scaralis quadricolor (Walker) (the type species of Alphinoides), Scaralis semilimpida (Walker), and Scaralis spectabilis (Walker). Diagnoses are given for separation of the genera Scaralis and Scaralina, as well as the subgenus Alphinoides, plus descriptions of and keys to all species of Scaralina north of Panama, as well as keys to the genera corresponding to the former subtribe “Calyptoproctina” occurring north of Panama.